Improved coordination of care after acute myocardial infarction in Poland since 2017: Promising early results. Issue 5 (May 2021) - Sagan, Anna; Rogala, Maciej; Buszman, Piotr P.; Kowalska-Bobko, Iwona
Highlights: Poland has had longstanding deficits in cardiac prevention and rehabilitation New coordinated care pathway after myocardial infarction was introduced in 2017 It comprises comprehensive rehabilitation, monitoring and secondary prevention and appears very promising In future, more emphasis should be put on primary cardiovascular disease prevention Abstract: A new model of complex patient care after acute myocardial infarction (AMI) has been in operation in Poland since late 2017, comprising invasive treatment, cardiac rehabilitation and scheduled outpatient follow-up. Its stated objectives are to improve secondary prevention measures, quality of care and long-term health outcomes in AMI-patients. The model implements all key aspects of post-MI care recommended by the European Society of Cardiology (ESC), representing the first nation-wide model of structured and comprehensive post-MI care that closely follows ESC guidelines. The aim of this paper is to describe the background of this reform, its content and implementation as well as to assess its results. Early outcomes seem promising, with significantly lower mortality rate and lower risk of serious cardiological events in patients participating in the new model of care compared to patients who were not included. A comprehensive assessment of the reform will require further clinical data, covering a larger population and a longer period of time, as well as a holistic analysis of the programme in its wider context, taking into account potential benefits and cost-effectiveness of improved primary prevention implemented outside of this model.